Short Movies as a Solution for Religious Moderation Education - Lestari, Afifah Dwi; Emeraldien, Fikry Zahria; Anggraeni, Arika; Zakiyah, Cici Nur (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Indonesia has six recognized religions written in the 1945 constitution. Such diversity triggers for people to be tolerant of one another and develop modernity among others. In truth, religious diversity also has a complex problem. A problem often arises when it comes to viewpoints between people of different religions. The problem also became more complex by promoting information that was not yet clearly the source of information. The correct method for solving the problem is education. Education can be made a guide in future problem solving and today's knowledge in the modern era, digitization is already a new life for society. Education in the digital age can reach you through the making of audiovisual, in this case, a short garage. A short film presentation is both exciting and encouraging for people in viewing the film industry to be enjoyed by a variety of people, the effectiveness of education using short films should be able to give Indonesian understanding of the importance of moderation in religion.